Age Related Increase of Intermuscular Adipose Tissue of the Thigh can be Prevented by Exercise in Sarcopenic Men - Engelke, Klaus; Chaudry, Oliver; Ghasemikaram, Mansour; Nagel, Armin Michael; Jakob, Franz; Kemmler, Wolfgang (JOURNAL OF BONE AND MINERAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-05-27

Changes in menopausal risk factors in early postmenopausal osteopenic women after 13 months of high-intensity exercise: The randomized controlled ACTLIFE-RCT - Hettchen, Michael; von Stengel, Simon; Kohl, Matthias; Murphy, Marie H.; Shojaa, Mahdieh; Ghasemikaram, Mansour; Bragonzoni, Laura; Benvenuti, Francesco; Ripamonti, Claudio; Benedetti, Maria Grazia; Julin, Mikko; Risto, Tapani; et al. (Clinical Interventions in Aging, 2021)
The menopausal transition is a critical period in women’s lives. Exercise might be the most promising non-pharmaceutic intervention to address the large variety of risk factors related to the pronounced estradiol decline during peri-and early-postmenopause. The aim of this study was to determine the effect of an 18-month multipurpose exercise program on risk factors and symptoms related to the menopausal transition. Fifty-four women 1–5 years postmenopause with osteopenia or osteoporosis were randomly assigned 1) to a high impact weight-bearing/high-intensity/velocity resistance training group (EG: n=27) exercising three times a week or 2) to an attendance control group (CG: n=27) that performed low-intensity exercise once a week. Both groups were supplemented with cholecalciferol and calcium. The primary study endpoint was bone mineral density (BMD) at lumbar spine (LS) and total hip, secondary outcomes were lean body mass (LBM), total and abdominal body percentage, metabolic syndrome Z-Score (MetS-Z), menopausal symptoms and muscle strength and power. Due to COVID-19, the study was stopped after 13 months. We observed significant effects for BMD-LS (EG: 0.002±.018 versus CG: −.009±0.018 mg/cm2, p=0.027) but not for BMD total hip (EG: −0.01±.016 versus CG: −.009±0.020 mg/cm2, p=0.129). LBM improved significantly in the EG and decreased in the CG (0.39±1.08 vs −0.37±1.34 kg, p=0.026). Total and abdominal body fat improved significantly in the EG and was maintained in the CG (−1.44±1.49 vs −0.02±1.55 kg, p=0.002 and-1.50±2.33 vs 0.08±2.07 kg, p=0.011). Significant effects in favor of the EG were also determined for menopausal symptoms (p=0.029), hip/leg extension strength (p<0.001) and power (p<0.001). However, changes of the MetS-Z did not differ significantly (p=0.149) between EG and CG. In summary, with minor exceptions, we demonstrated the effectiveness of a multipurpose exercise protocol dedicated to early-postmenopausal women on various risk factors and complaints related to the menopausal transition.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Bone mineral density; Early postmenopause; Multipurpose exercise

Detraining Effects on Muscle Quality in Older Men with Osteosarcopenia. Follow-Up of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) - Ghasemikaram, Mansour; Engelke, Klaus; Kohl, Matthias; von Stengel, Simon; Kemmler, Wolfgang (Nutrients, 2021)
The present study aimed to determine the effect of detraining on muscle quality (MQ) in older men with osteosarcopenia. Forty-three community-dwelling older men (78 ± 4 years) were randomly allocated to a consistently supervised high-intensity resistance exercise training (HIRT) group (n = 21) or a control group (CG, n = 22). The HIRT scheduled a periodized single set protocol twice weekly. After the intervention, the men were subjected to six months of detraining. Muscle quality (MQ), defined as maximum isokinetic hip/leg extensor strength per unit of mid-thigh intra-fascia volume, was determined by magnetic resonance imaging (MRI) or per unit of thigh muscle mass assessed by dual-energy X-ray absorptiometry (DXA). Intention-to-treat analysis with multiple imputations was applied. We observed significant exercise effects for MQ (p = 0.001). During detraining, the HIRT group lost about one-third of the intervention-induced gain and displayed significantly (p = 0.001) higher MQ reductions compared to the CG. Nevertheless, after training and detraining, the overall intervention effect on MQ remained significant (p ≤ 0.004). In summary, six months of absence from HIRT induce a significant deleterious effect on MQ in older osteosarcopenic men. We conclude that intermitted training programs with training breaks of six months and longer should be replaced by largely continuous exercise programs, at least when addressing MQ parameters.
CRIS-Team Scopus Importer:2021-06-18
Keywords: detraining; exercise training; muscle mass; muscle strength; resistance training

EFFECT OF AGEING ON FAT INFILTRATION OF THIGH AND PARASPINAL MUSCLES IN MEN - Engelke, Klaus; Ghasemikaram, Mansour; Chaurdy, O.; Uder, Michael; Nagel, Armin Michael; Jacob, F.; Kemmler, Wolfgang (AGING CLINICAL AND EXPERIMENTAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-10-14

Effects of 16 months of high intensity resistance training on thigh muscle fat infiltration in elderly men with osteosarcopenia - Ghasemikaram, Mansour; Chaudry, Oliver; Nagel, Armin Michael; Uder, Michael; Jakob, Franz; Kemmler, Wolfgang; Kohl, Matthias; Engelke, Klaus (GeroScience, 2021)
Osteosarcopenia is characterized by a progressive decline in muscle function and bone strength and associated with muscle fat accumulation. This study aimed to determine the effect of long-term high intensity resistance training (HIRT) on thigh muscle fat infiltration in older men with osteosarcopenia. Forty-three community-dwelling men (72 years and older) were randomly assigned to either an exercise group (EG, n = 21) or an inactive control group (CG, n = 22). EG participants performed a supervised single-set exercise training with high effort two times per week. Participants of both groups were individually provided with dietary protein to reach a cumulative intake of 1.5-1.6 g/kg/day or 1.2-1.3 g/kg/day (EG/CG), respectively, and Up to 10,000 IE/week of Vitamin-D were supplemented in participants with 25 OH Vitamin-D 3 levels below 100 nmol/l. Magnetic resonance (MR) imaging was performed to determine muscle and adipose tissue volume and fat fraction of the thigh. At baseline, there were no significant differences between the two groups. After 16 month,, there were significant training effects of 15% (p = 0.004) on intermuscular adipose tissue (IMAT) volume, which increased in the CG (p = 0.012) and was stable in the EG. In parallel, fat fraction within the deep fascia of the thigh (Baseline, EG: 18.2 vs CG: 15.5, p = 0.16) significantly differed between the groups (Changes, EG: 0.77% vs. CG: 7.7%, p = 0.009). The study confirms the role of fat infiltration of the muscles as an advanced imaging marker in osteosarcopenia and the favorable effects of HIRT on adipose tissue volume of the thigh, in men with osteosarcopenia.
CRIS-Team WoS Importer:2021-02-05

Effects of High-Intensity Aerobic Exercise and Resistance Training on Cardiometabolic Risk in Early-Postmenopausal Women - Hettchen, Michael; von Stengel, Simon; Kohl, M.; Murphy, M. H.; Shojaa, Mahdieh; Ghasemikaram, Mansour; Bragonzoni, L.; Benvenuti, F.; Ripamonti, C.; Benedetti, G.; Julin, M.; Risto, T.; et al. (Deutsche Zeitschrift für Sportmedizin, 2021)
Purpose: The menopausal transition is a critical period in wo-men’s lives. The central aim of the present study was to evaluate the effect of a multimodal exercise protocol on the cardiometa-bolic risk factor potentially related to menopausal transition in early postmenopausal women. Methods: Fifty-four (54) early-postmenopausal women (54.0±1.8 years) were randomly assigned to two groups: (1) exercise group (EG: n=27) which conducted a high intensity aerobic and resistance training three times/week and (2) active control group (CG: n=27) exercising once a week with low exercise inten-sity. Besides bone density, the main variable of this project, the outcome variable in this thesis was also cardiometabolic risk, as summarized by the Metabolic Syndrome (MetS) Z-Score. We applied Intention-to-Treat (ITT) and Per Protocol Analyses (PPA) with multiple imputation and used standardized mean differences to illustrate the effects. Results: After 16 weeks of exercise two participants (EG: n=1; CG: n=1) were lost to follow-up. Effects for the MetS Z-Score were moderate (EG:-0.36±1.36 vs. CG: 0.51±2.28; SMD: 0.47, 95% CI:-0.08 to 1.03), albeit borderline non-significant (ITT: p=.089; PPA: p=.060). Conclusion: The present multimodal exercise protocol just fai-led to affect the MetS Z-Score and its underlying cardiometabolic risk factors. Whether this result can be generalized to the entire cohort of early-postmenopausal women or whether it has to be attributed to the only moderately high exercise intensity during the early weeks of the intervention along with a relatively short intervention period remains to be evaluated.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Menopausal transition; Metabolic syndrome; MetS Z-Score

Effects of high-intensity training on fatty infiltration in paraspinal muscles in elderly males with osteosarcopenia – the randomized controlled FrOST study - Kircher, Kaja; Chaudry, Oliver; Nagel, Armin Michael; Ghasemikaram, Mansour; Uder, Michael; Jakob, Franz; Kohl, Matthias; Kemmler, Wolfgang; Engelke, Klaus (BMC Geriatrics, 2024)
Background: Osteosarcopenia is a common geriatric syndrome with an increasing prevalence with age, leading to secondary diseases and complex consequences such as falls and fractures, as well as higher mortality and frailty rates. There is a great need for prevention and treatment strategies. Methods: In this analysis, we used magnetic resonance imaging (MRI) data from the randomised controlled FrOST trial, which enrolled community-dwelling osteosarcopenic men aged > 72 years randomly allocated to 16 months of twice-weekly high-intensity resistance training (HIRT) or a non-training control group. MR Dixon imaging was used to quantify the effects of HIRT on muscle fat infiltration in the paraspinal muscles, determined as changes in muscle tissue, fat faction and intermuscular adipose tissue (IMAT) in the erector spinae and psoas major muscles. Intention-to-treat analysis with multiple imputation was used to analyse the data set. Results: After 16 months of intervention, 15 men from the HIRT and 16 men from the CG were included in the MRI analysis. In summary, no positive effects on the fat infiltration of the erector spinae and psoas major muscles were observed. Conclusions: The previously reported positive effects on lumbar spine bone mineral density (BMD) suggest that mechanotransduction induces tropic effects on bone, but that fat infiltration of the erector spinae and psoas major muscles are either irreversible or, for some unknown reason, resistant to exercise. Because of the beneficial effects on spinal BMD, HIRT is still recommended in osteosarcopenic older men, but further research is needed to confirm appropriate age-specific training exercises for the paraspinal muscles. The potential of different MRI sequences to quantify degenerative and metabolic changes in various muscle groups must be better characterized. Trial registrations: FrOST was approved by the University Ethics Committee of the Friedrich-Alexander University of Erlangen-Nürnberg (number 67_15b and 4464b) and the Federal Office for Radiation Projection (BfS, number Z 5–2,246,212 – 2017–002). Furthermore, it fully complies with the Declaration of Helsinki and is registered at ClinicalTrials.gov: NCT03453463 (05/03/2018). JAMA 310:2191–2194, 2013.
CRIS-Team Scopus Importer:2024-02-23
Keywords: BMD; Dixon imaging; HIRT; IMAT; MRI; Osteosarcopenia

Once Weekly Whole-Body Electromyostimulation Enhances Muscle Quality in Men: Data of the Randomized Controlled Franconian Electromyostimulation and Golf Study - Zink-Rückel, Carina; Chaudry, Oliver; Engelke, Klaus; Ghasemikaram, Mansour; Kohl, Matthias; Uder, Michael; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
Whole-body electromyostimulation (WB-EMS) is commercially advertised as a time-efficient resistance-type exercise technology. Indeed, the commercial, non-medical setting applies 20 min of WB-EMS only once a week. However, this setting conflicts with the approved scientific approach of higher training frequencies. Using data from an ongoing study on WB-EMS and golf performance as a vehicle, we evaluate the effect of once weekly WB-EMS on changes of fatty muscle infiltration, as a crucial parameter of muscle quality. Fifty-four moderately physically active male amateur golfers 18–70 years old were randomly allocated to a WB-EMS (n = 27) with a standard setting of once weekly 20 min and a non-WB-EMS control group (CG, n = 27). Intermuscular adipose tissue (IMAT) volume and intrafascial muscle tissue (MT) volume per unit of intrafascial volume as determined by magnetic resonance imaging were used to characterize muscle quality. Intention to treat analysis with multiple imputation was applied. WB-EMS was conducted at the participants’ homes; thus, the attendance rate was close to 100%. After 16 weeks of intervention, we observed increases in volume-adjusted IMAT (p = 0.040) and decreases in MT (p = 0.206) in the CG. IMAT decreased in the WB-EMS group (p = 0.215), while MT increased significantly (p = 0.032). Of importance, group difference (i.e., “effects”) for intra-group changes in volume-adjusted IMAT (effect size: d´ = 0.66; p = 0.028) and MT (d´ = 0.70; p = 0.020) was significant for both parameters. Once weekly WB-EMS application significantly affects muscle quality of the mid-thigh in moderately active, healthy men 18–70 years old.
CRIS-Team Scopus Importer:2021-08-13
Keywords: fatty muscle infiltration; men; muscle quality; muscle tissue; whole-body electromyostimulation

The effect of ageing on fat infiltration of thigh and paraspinal muscles in men - Engelke, Klaus; Ghasemikaram, Mansour; Chaudry, Oliver; Uder, Michael; Nagel, Armin Michael; Jakob, Franz; Kemmler, Wolfgang (Aging Clinical and Experimental Research, 2022)
Background Myosteatosis, skeletal muscle fat infiltration, is associated with inflammation and fibrosis. The age-related increase of myosteatosis is an important characteristic of sarcopenia and contributes to fragility. Aims To investigate the impact of healthy aging on intermuscular adipose tissue (IMAT) and muscle fat fraction (FF) in the thigh and the paraspinal muscles in males. Methods In 54 healthy males (age 20-70), all active hobby golfers, magnetic resonance imaging was performed to determine volume of IMAT, volume of muscle tissue (MT) and of percentage of FF. Results Between ages 20-70, at the thigh, IMAT/MT volume and MT FF increased annually by 2.9% and 1.3%, respectively. At the psoas IMAT/Psoas volume did not change with age. MT FF increased by 1.5% annually. At the erector spinae IMAT/Erector volume decreased by 0.3% and MT FF increased by 2.8% annually. Discussion With increasing age, in males, thigh muscle atrophied, muscle tissue was partly replaced by adipose tissue and remaining muscle tissue also contained more fat. Similar effects were observed in the erector spinae. The psoas muscle did not atrophy, although MT FF also increased with age. Overall correlations with age were weak to moderate with higher correlations observed in the paraspinal muscles. Conclusions Age-related increases of muscle fat infiltration were observed in the thigh and in the spine. Muscle atrophy did not occur in the psoas. In cross-sectional studies, an adjustment of volumetric parameters by muscle volume is advisable when comparing age-dependent results.
CRIS-Team WoS Importer:2022-06-10
Keywords: MRI; Thigh; Erector spinae; Psoas; IMAT; Muscle fat fraction